A spatiotemporal analysis of droughts and the influence of North Atlantic Oscillation in the Iberian Peninsula based on MODIS imagery - Mühlbauer, Stefan (2019)
Mühlbauer, S., Costa, A. C., & Caetano, M. (2016). A spatiotemporal analysis of droughts and the influence of North Atlantic Oscillation in the Iberian Peninsula based on MODIS imagery. Theoretical And Applied Climatology, 124(3-4), 703-721. https://doi.org/10.1007/s00704-015-1451-9